Development and internal validation of a prognostic nomogram for recurrence in chronic rhinosinusitis with nasal polyps after functional endoscopic sinus surgery - Yang Yang; Congli Geng; Jiahua Luo; Min Wang; Xiaopei Yuan; Yan Liu; Shichang Li; Zhimin Xing (Frontiers in Medicine, 2026)
Objectives Chronic rhinosinusitis with nasal polyps (CRSwNP) frequently recurs after functional endoscopic sinus surgery (FESS). This study aimed to develop and internally validate a prognostic nomogram for predicting the two-year recurrence-free rate (RFR) in patients with CRSwNP after FESS. Methods A total of 404 patients with CRSwNP who underwent FESS were retrospectively enrolled and randomly divided into a training cohort (n = 303) and an internal validation cohort (n = 101). Recurrence was defined as the first postoperative detection of nasal polyps by nasal endoscopy within 2 years. Candidate predictors were selected using LASSO Cox regression and further evaluated using multivariate Cox regression. A nomogram was constructed to predict the two-year RFR. Results During the two-year follow-up, 148 patients experienced recurrence. Five independent predictors were included in the final model: number of previous nasal surgeries, olfactory cleft polyp, Lund–Mackay score, peripheral blood eosinophil percentage, and tissue eosinophil percentage. The nomogram showed good discrimination, with C-indices of 0.751 (95% CI, 0.707–0.795) in the training cohort and 0.707 (95% CI, 0.625–0.789) in the internal validation cohort. Calibration curves demonstrated good agreement between predicted and observed two-year RFR. Risk stratification based on the nomogram score separated patients into low-, intermediate-, and high-risk groups with significantly different RFRs. Conclusion We developed and internally validated a nomogram for estimating two-year recurrence-free rate in patients with CRSwNP after FESS. The nomogram will help identify patients at high risk of recurrence and assist in the development of individualized treatment plans for patients with CRSwNP. Furthermore, we found that olfactory cleft polyps were a new independent risk factor for the postoperative recurrence of CRSwNP.